2021
DOI: 10.1016/j.jor.2021.07.016
|View full text |Cite
|
Sign up to set email alerts
|

Chronicling the effect of COVID-19 on orthopedic literature

Abstract: Background The novel coronavirus disease (COVID-19) has had a significant impact on orthopedic surgery practice, but there has been little investigation of the effects of COVID-19 on the orthopedic surgery literature. Additionally, because orthopedic research plays a vital role in physician education, changes to the characteristics and content of published literature can have lasting impacts on future teaching and learning. This paper represents the first known analysis of the COVID-19 pandemic's … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…The largest limitation of this study is that there is not a strong control group to compare our results to. There are similar published data from other subspecialties that were affected by the COVID-19 pandemic (plastic surgery, orthopedic surgery, and oral-maxillofacial surgery); however, the most valuable data would be from subspecialties that are inherently more similar to anesthesiology (general surgery, internal medicine/critical care medicine, and pediatrics) [ 13 , 15 , 16 ]. Additionally, in this study, we elected to study the AAS as a continuous variable.…”
Section: Reviewmentioning
confidence: 87%
See 1 more Smart Citation
“…The largest limitation of this study is that there is not a strong control group to compare our results to. There are similar published data from other subspecialties that were affected by the COVID-19 pandemic (plastic surgery, orthopedic surgery, and oral-maxillofacial surgery); however, the most valuable data would be from subspecialties that are inherently more similar to anesthesiology (general surgery, internal medicine/critical care medicine, and pediatrics) [ 13 , 15 , 16 ]. Additionally, in this study, we elected to study the AAS as a continuous variable.…”
Section: Reviewmentioning
confidence: 87%
“…When compared to other specialties, anesthesiology had noticeably more literature published about COVID-19 than others [ 13 , 15 , 16 ]. In our study, COVID-19 literature represented 12% (676) of the total number of articles investigated, whereas a similar study conducted in plastic surgery literature identified that only 3.2% (220) of the total articles involved COVID-19 [ 13 ].…”
Section: Reviewmentioning
confidence: 99%
“…Owing to the global pandemic, experiences and recommendations soon began to be published in orthopaedic journals [ 14 , 15 ]. Orthopaedics, as a representative of elective care, was perhaps influenced by most of the disciplines in the field of elective surgery.…”
Section: Discussionmentioning
confidence: 99%
“…We selected 15 ophthalmology journals with the highest impact factor in 2020, as determined by Journal Citation Reports. Utilizing an advanced PubMed search, [2][3][4] we identified all articles (n = 8609) published among these journals from January 1, 2020, to October 17, 2021. Manuscripts pertaining to the COVID-19 pandemic were initially included if their titles included "COVID," "pandemic," "SARS," "corona," "nCoV," For articles where data were available (n = 175), median time from submission to publication (either print or online) was 44 days, which is substantially quicker than publication times reported before the COVID-19 pandemic.…”
Section: Assessing the Impact Of The Covid-19 Pandemic On The Ophthal...mentioning
confidence: 99%
“…We selected 15 ophthalmology journals with the highest impact factor in 2020, as determined by Journal Citation Reports . Utilizing an advanced PubMed search,2–4 we identified all articles (n=8609) published among these journals from January 1, 2020, to October 17, 2021. Manuscripts pertaining to the COVID-19 pandemic were initially included if their titles included “COVID,” “pandemic,” “SARS,” “corona,” “nCoV,” or “COVID-19.” All articles were further screened manually to confirm appropriate categorization.…”
mentioning
confidence: 99%